The cognitive psychology of planning - Morris, Robin, 1958-; Ward, Geoff, 1968- (Current issues in thinking & reasoning., 2005)
What are the cognitive processes involved in formulating, evaluating and selecting a sequence of thoughts and actions to achieve a goal? This book evaluates the different approaches to the scientific study of planning.